Association between decreased expression of estrogen receptor alpha, androgen receptor and phosphatase and tensin homolog immunoexpression in the canine prostate - Kobayashi, Priscila E. [UNESP]; Rodrigues, Marcela M.P. [UNESP]; Gartner, Fatima; Rema, Alexandra; Fonseca-Alves, Carlos E. [UNESP]; Laufer-Amorim, Renée [UNESP] (FapUNIFESP (SciELO), 2019)
Canine prostate gland is a hormonal dependent organ and its imbalance of estrogen and androgen receptor expressions are directly associated with the development of different diseases. Due to the lack of information regarding the behavior of the aforementioned receptors in canine prostate cancer (PC), this study aimed to identify estrogen receptor alpha (ERα), androgen receptor (AR), Ki67 and phosphatase and tensin homolog (PTEN) protein expressions in canine PC by immunohistochemistry. We found nuclear expression of ERα and AR in the epithelial cells of normal canine samples and a loss of protein expression in PC samples. Normal samples showed Ki67 expression in a few basal cells and the PC samples showed the highest mean of positive cells (253.1). Canine prostate cancer showed a high proliferative index, which was associated with independence of hormonal actuation. PTEN showed positive nuclear and cytoplasmic expression in normal canine samples and a loss in PC. Loss of ERα, AR and PTEN indicated that canine PC exhibits the same immunohistochemical phenotype as in human patients with PC resistant to hormonal therapy. Therefore, canine PC should be considered as a model to study human PC resistant to hormonal therapy.
Keywords: Androgen receptor; Canine prostate; Dogs; Hormonal receptors; Immunoexpression; Immunohistochemistry; INDEX TERMS: Estrogen receptor alpha; Phosphatase; Prostate lesions; PTEN; Tensin homolog